XPS, AES and Auger parameter of Pd and PdO - Brun, M; Berthet, A; Bertolini, J.C (Journal of electron spectroscopy and related phenomena, 1999)
Auger and X-ray photoelectron spectra of palladium and palladium oxide were recoded with a MgKα primary X-ray source. The Pd3d 5/2 binding energies are 335.4 eV and 336.8 eV for Pd and PdO respectively. While the most widely used M 4,5 VV Auger structure is rather well defined for pure Pd, with a peak maximum measured at a kinetic energy of 327.5 eV, this is not the case for PdO. Consequently, it is difficult to compare the Pd3d-MVV Auger parameters of these two compounds. This is mainly due to the strong changes evidenced in the structure of the valence band. On the contrary. the shape of the less intense M 4,5N 2,3N 2,3 Auger peak, which implies only the Pd3d and the Pd4p core levels, does not change much between Pd and PdO. The maximum of the MNN Auger peak is measured at 242.8 eV and 240.5 eV for Pd and PdO respectively.